The main issues of the individuals’ deposits guarantee Fund in the conditions of bankruptcies of Ukrainian banks - Юрик, Світлана Олександрівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
For the normal functioning of Fund of guaranteeing of holding of physical persons it is necessary to expose his problems in-process in the modern terms of unstable development of economy. These problems grow at further bankruptcy of banks. Certain problems of fund, his mutual relations with a regulator and influence of normative base on his functioning, and also the ways of overcoming of these problems are offered.